2022
DOI: 10.25259/sni_66_2022
|View full text |Cite
|
Sign up to set email alerts
|

Novel case of primary intracranial solitary plasmacytoma presenting with significant intratumoral hemorrhage

Abstract: Background: Solitary plasmacytoma is a localized lesion comprising monoclonal neoplastic proliferation of plasma cells. This disease is rarely encountered and few reports have described primary intracranial solitary plasmacytoma (PISP). Case Description: We report a case of PISP that presented initially as status epilepticus and exhibited massive intratumoral hemorrhage at the subcortical area. To the best of our knowledge, this is the first recorded presentation of this pathology in this manner. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…20,22 In cases where the tumor does not spread continuously with the bone or dura mater, leptomeningeal or hematogenous spread is considered to be related to tumor bleeding owing to its richness of blood flow. 18,20,22 In this case, CSF cytology was initially negative, and no other significant lesions appeared on whole-spine MRI. However, the initial finding of the CSF was bloody, suggesting leptomeningeal or hematogenous spread with potential tumor bleeding, which could account for the multiple CNS lesions, including the intraparenchymal lesions.…”
Section: Pattern Of Occurrence and Progression Of Multiple Cns Oiia-lpdmentioning
confidence: 64%
See 3 more Smart Citations
“…20,22 In cases where the tumor does not spread continuously with the bone or dura mater, leptomeningeal or hematogenous spread is considered to be related to tumor bleeding owing to its richness of blood flow. 18,20,22 In this case, CSF cytology was initially negative, and no other significant lesions appeared on whole-spine MRI. However, the initial finding of the CSF was bloody, suggesting leptomeningeal or hematogenous spread with potential tumor bleeding, which could account for the multiple CNS lesions, including the intraparenchymal lesions.…”
Section: Pattern Of Occurrence and Progression Of Multiple Cns Oiia-lpdmentioning
confidence: 64%
“…In the first place, primary CNS plasmacytoma with intraparenchymal lesion that presents as EP is rare. [17][18][19][20] Additionally, cases of OIIA-LPD presenting as EP are rarely reported. 21 In this case, there were multiple CNS lesions including an intraparenchymal lesion in the left temporal lobe, and the pathological diagnosis was plasmacytoma.…”
Section: Pattern Of Occurrence and Progression Of Multiple Cns Oiia-lpdmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional imaging usually shows homogeneously enhancing soft tissue masses [24]. While literature review provides a few cases describing intracranial plasmocytoma, they have all been reported as extraaxial masses in patients suffering from multiple myeloma [25][26][27]. To our knowledge, this is the first case report presenting a patient with an intra-axial solitary plasmacytoma that shows no connection to the dura or skull interface on cross-sectional imaging.…”
Section: Extramedullary Plasmacytomamentioning
confidence: 91%